Empowering motivation: the journey of wheelchair basketball athletes to overcome constraints - Sarol, Halil (Frontiers in Psychology, 2024)
The aim of this phenomenological study is to determine the motivational factors in the participation of wheelchair basketball players in sports according to Self-Determination Theory. Methods: The study group of the research was determined by the criterion sampling method, which is one of the purposeful sampling methods. Accordingly, thirteen (13) wheelchair athletes constituted the study group. In the research, a personal information form and a semi-structured interview form were prepared as data collection tools within the framework of the self-determination theory. Interviews were conducted face-to-face with the prepared interview forms. The data were analyzed by reflexive thematic analysis method. Results: Six (6) themes emerged: constraints, coping strategies, appreciation, positive feedback, need for existence, and development. Sixteen sub-themes related to these themes were identified. Conclusion: The most significant factors causing a lack of motivation in wheelchair basketball athletes were observed to be structural constraints such as access to materials and facilities. Extrinsic sources of motivation were identified as the positive attitudes and behaviors of individuals in their environment, often related to admiration, appreciation, and being set as an example, and this situation has a positive impact on wheelchair basketball athletes. On the other hand, it can be stated that intrinsic motivations such as identity change, gaining self-confidence, and the feeling of success are crucial in overcoming constraints through sports participation. 1 'Figure 1 near here' Yukarı taşındı [1]: Sports play a role in preventing the exclusion 83 of individuals with disabilities from participating in activities, just 84 like their peers without disabilities, and have an impact on their 85 psychological well-being (Moss et al., 2020; Koçak et al., 2023).